2023
DOI: 10.1111/scs.13148
|View full text |Cite
|
Sign up to set email alerts
|

Acute outreach service to nursing homes: A systematic review with GRADE and triple aim approach

Abstract: Background People living in nursing homes face the risk of visiting the emergency department (ED). Outreach services are developing to prevent unnecessary transfers to ED. Aims We aim to assess the performance of acute care services provided to people living in nursing homes or long‐term homecare, focusing on ED transfer prevention, safety, cost‐effectiveness and experiences. Materials & Methods This review was guided by the Preferred Reporting Items for Systematic Reviews and Meta‐Analyses (PRISMA). Studies w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 45 publications
(100 reference statements)
0
1
0
Order By: Relevance
“…There is wide heterogeneity in the nature of the interventions and the professionals used in these units. Our recently published review concluded that while previously published data might favour the adoption of acute outreach services with preventive components, the effectiveness of solely acute outreach services in reducing hospitalisations and ED transfers remains uncertain [23]. We found no studies investigating the impact of outreach service units, such as LiiSa, on emergency medical services (EMSs).…”
Section: Introductionmentioning
confidence: 99%
“…There is wide heterogeneity in the nature of the interventions and the professionals used in these units. Our recently published review concluded that while previously published data might favour the adoption of acute outreach services with preventive components, the effectiveness of solely acute outreach services in reducing hospitalisations and ED transfers remains uncertain [23]. We found no studies investigating the impact of outreach service units, such as LiiSa, on emergency medical services (EMSs).…”
Section: Introductionmentioning
confidence: 99%